Acknowledging the Intersectionality of Geoscientists With Disabilities to Enhance Diversity, Equity, Inclusion, and Accessibility - Ian O. Castro; Christopher L. Atchison (Earth Science, Systems and Society)
The geosciences have implemented a variety of efforts designed to strengthen diversity, equity, inclusion, and accessibility (DEIA) of underrepresented groups. While these efforts have had substantial financial investment, recruitment and retention for underrepresented individuals has yet to reflect this. To improve the resources available for underrepresented scholars, the geoscience community must expand its exploration of identity beyond a singular construct, and instead focus on how identities intersect. In this exploratory study, the framework of intersectionality will be highlighted to better understand the convergence of disability with other underrepresented identities in the geoscience disciplines. Major themes of social inclusion and belonging, power, safety, and opportunity are presented through the lived experiences of geoscientists, along with recommendations on expanding broadening participation efforts for underrepresented individuals in the geosciences.